The Certain Generalized Stresses Method for static analysis of multilayered composite plates with variability of material and physical properties. (15th April 2016) - Yin, Qi; Druesne, Frédéric; Lardeur, Pascal
Abstract: In this paper, the Certain Generalized Stresses Method (CGSM) is developed for static probabilistic analysis of multilayered composite plates modeled by finite elements. The material and the physical properties are considered as random parameters. The variability of a displacement can be evaluated by a Monte Carlo Simulation (MCS) using an explicit expression. For calculating the variability of a displacement, only one nominal finite element analysis with two load cases is required. The variability of strains, stresses and failure criteria can also be evaluated by using the CGSM. Two examples, a two-layer bending plate and an eight-layer bending plate, are studied. The results are compared with those obtained by the direct MCS, considered as a reference, and those presented in the literature. The comparison shows that the CGSM + MCS approach provides quite accurate results and highlights the high computational efficiency of the proposed method.